Kontribusi Filsafat Stoikisme pada PAK dalam mengembangkan Konsep Diri Self-Love bagi Perempuan di Era Digitalisasi - Delinda Elizabeth Aritonang; Fernando Dapot Hamonangan L Tobing (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2023)
This article aims to show the contribution of the philosophy of stoicism in Christian religious education to the development of self-love for Christian women. In this era of digitalization, many Christian women experience decadence in their self-confidence and dilemmas with the concept of loving themselves, which causes problems for themselves and problems for others. The research method used in this research is a qualitative research method with a literature study approach. This method divides this research into three important points. First, the philosophy of Stoicism in the era of digitalization. Second, the self-concept of self-love for women Third, the philosophy of Stoicism in developing the self-concept of self-love for women as a contribution to Christian religious education. The results of this research show that the philosophy of stoicism can be implemented in Christian religious education for the lives of Christian women by developing the self-concept of self-love through a loving attitude, living a life full of happiness, being grateful for the life that women have, and being able to manage each problem well themselves and with others.